Dietary patterns, nutritional profile, and body mass index in Mexican schoolchildren: A cross-sectional study - Zamora-Gasga, Victor Manuel; Montalvo-González, Efigenia; Loarca-Piña, Guadalupe Flavia; Chacón-López, Alejandra Martina; Tovar, Juscelino; Sáyago-Ayerdi, Sonia Guadalupe (Archivos Latinoamericanos de Nutrición (ALAN), 2020)
Childhood obesity is a serious public health problem in Mexico. In this study, childhoodspecific dietary patterns and their relationship with overweight-obesity prevalence, nutrient profiles and types of foods consumed were studied. A descriptive cross-sectional study of 724 randomly selected schoolchildren between 9 to 12 years old from Nayarit State, Mexico was performed. Data on anthropometric characteristics and food intake were recorded. Seven dietary patterns and three specific diets were identified by multivariate analysis. A dietary pattern characterized by high legume, snack and low beverage intake was negatively associated with weight and body mass index. The overall overweight and obesity prevalence was 20.2% and 20.6%, respectively. Diet type significantly influenced (p<0.05) protein, carbohydrates and fat intake but did not show correlation with the overweightobesity status. Simple sugars, candies, pastries and sweetened beverages appeared in all dietary patterns. Dietary patterns in countries with a wide gastronomic diversity should be considered to design preventive nutrition intervention programs. La obesidad infantil es un problema de salud pública en México. En este trabajo, se estudiaron los patrones dietéticos de escolares mexicanos y su relación con la prevalencia de sobrepeso-obesidad, el perfil de nutrientes y los principales grupos de alimentos consumidos. Se llevó a cabo un estudio transversal descriptivo donde participaron 724 escolares seleccionados al azar de entre 9 a 12 años del Estado de Nayarit, México evaluándose las características antropométricas y la ingesta de alimentos. Siete patrones dietéticos y tres dietas específicas fueron identificados mediante análisis multivariado. Un patrón de dieta caracterizada por una alta ingesta de legumbres y aperitivos junto con una baja ingesta de bebidas azucaradas se asoció negativamente con el peso e índice de masa corporal. La prevalencia de sobrepeso y obesidad fue del 20.2 y 20.6%, respectivamente. El tipo de dieta influyó significativamente (p<0.05) en la ingesta de proteínas, hidratos de carbono y el consumo de grasas, pero no mostró correlación con la condición de sobrepeso-obesidad. Los azúcares simples, dulces, postres y bebidas endulzadas aparecieron en todos los patrones dietéticos. Los patrones dietéticos en los países con una gran diversidad gastronómica podrían ser considerados de interés para diseñar programas de intervención nutricional preventiva.